Severe adverse reactions to benzathine penicillin G in rheumatic heart disease: A systematic review and meta-analysis - Eshetie Melese Birru; Kefyalew Addis Alene; Laurens Manning; Kevin T. Batty; Brioni R. Moore (PLoS ONE, 2025)
Background Fear of severe adverse reaction (SAR) and reluctance of health care providers to administer intramuscular injections are major contributing factors to poor adherence of benzathine penicillin G (BPG) in the management of rheumatic heart disease (RHD). However, data on the risk of SARs following BPG injections for RHD are relatively limited and inconclusive. Our systematic review and meta-analysis aimed to evaluate the incidence of SARs associated with BPG injections used for secondary prophylaxis of RHD. Methods A systematic literature search of PubMed, Scopus and Web of Science databases was conducted to identify relevant studies reporting adverse reactions following BPG injections in patients with acute rheumatic fever (ARF) and/or RHD. A random effect meta-analysis was performed to estimate the pooled incidence of SARs. Result Nine studies (eight cohort and one randomized controlled trial), comprising 11,587 participants and > 154,760 BPG injections, were included in the analysis. The pooled incidence of SARs was 9.7 per 10,000 cases (95% CI: 0.1–29.2) and 1.1 per 10,000 BPG injections (95% CI: 0.4–2.2). Six fatal reactions were reported (0.05% of patients and 24% of SARs), all occurring in patients with severe RHD. Conclusion SARs following BPG injections in patients with ARF or RHD are rare. Our findings highlight the importance of balancing the low rate of SARs against the benefits of BPG in secondary prophylaxis for RHD, particularly in high-risk populations. High-quality longitudinal research and comprehensive adverse reaction reporting are essential to address safety concerns among healthcare providers and patients that impact BPG delivery.